PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE WARDAH DI KECAMATAN CIHAMPELAS - Arisma, Arisma; Zulestiana, Dinda Amanda (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to examine the contribution of price and product quality to purchasing decisions for Wardah Skincare in the Cihampelas area. Data were obtained from an online questionnaire from 96 participants using purposive sampling, and multiple linear regression analysis was performed. The study found that, to a certain extent, product quality (t-test = 3.960) and price (t-test = 2.076)have a significiant effect purchasing decisions. Each independent variable contributes simultaneously to purchasing decisions (F-test = 18.471). The R-squared value was 28.4%, indicating that the independent variables contributed 28.4%. The difference was attributed to factors outside the discussion Keywords: Price; Product Quality; Purchasing Decision; Wardah; Skincare